Sustainable Energy Recovery From the Malaysian Coal Bottom Ash and the Effects of Fineness in Improving Concrete Properties - Beddu, Salmia; Abd Manan, Teh Sabariah Binti; Mohamed Nazri, Fadzli; Kamal, Nur Liyana Mohd; Mohamad, Daud; Itam, Zarina; Ahmad, Mushtaq (Frontiers in Energy Research, 2022)
The particle size (µm) of coal bottom ash (CBA) displayed significant effects on the concrete engineering properties. This research aims to assess the improvement on engineering properties of concrete containing CBA (fineness: 75 and 100 µm) known as Mix 75 and Mix 100; and to optimize the percentage of CBA as supplementary cement materials (SCM) in concrete. The physicochemical properties of CBA were analysed using X-ray fluorescence (XRF), X-ray diffraction (XRD), particle size distribution (PSD), and scanning electron microscope (SEM). The strength of concrete was determined based on workability, compressive and splitting tensile strengths. The concrete strength improvement was optimized using response surface methodology (RSM). Based on XRF analysis, fly ash (FA) and CBA can be classified as Class F based on ASTM 1994 and CSA A3001. The XRD analysis showed that, CBA were rich in silicates based on the highest peak at 45°. The mean particle size of 45 and 75 µm CBA were 27.91 and 26.88 µm. The SEM images showed that CBA has few cenospheres, and components of irregular-shaped of char particles. The slumps were of collapse type. The compressive strength of concrete increased with the number of curing days. The splitting tensile strengths in 28 curing days gradually decreased with an increase of CBA. The optimal percentage of CBA in Mix 75 is equivalent to 6% within 45.4 curing days producing 40 MPa of compressive strength. Meanwhile, the optimal percentage of CBA in Mix 100 is equivalent to 12% within 51 curing days producing 50 MPa of compressive strength. Based on the validation of optimized model, the period of 28 curing days was found to be the best duration for curing of Mix 75 (for 5, 10, and 15% of CBA) and Mix 100 (for all percentages of CBA, 5, 10, 15, 20, 25, and 30%). The error percentages were observed to be within the acceptable ranges for 28 (3.53 to 12.11%), and 56 (0.34 to 11.62%) curing days.